Gender Gap pada Tingkat Partisipasi Kerja di Provinsi DKI Jakarta - Anas, Azwar; Damayanti, Maria Goreti Arie (UI Scholars Hub, 2020)
This research aims to decompose the employment participation rate to explain gender gap in DKI Jakarta Province in three periods (1995, 2005, and 2015). Determinant of employment participation rate of men and women was estimated by probit regression model and marginal effect. Non-linear decomposition technique used to analyze the source of gender gap. The results show that the main cause of gender gap comes from structural factors in the labor market (discrimination). The value of the gender gap in 20 years has decreased, in 1995, 2005, and 2015 it was 40,82%; 39,17%; and 29,34% respectively. It shows that the discrimnination rate in Jakarta has decreased.